Sugar intake of young children in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Bhula, Jayshree (Massey University, 2023)
Background: Sugar intake has been linked to noncommunicable diseases such as overweight, obesity, type 2 diabetes, and dental caries in children. In New Zealand, the prevalence of child obesity is increasing, especially amongst Māori and Pasifika, and dental caries are reported in young children. Demographic characteristics and feeding practices have been linked to poor nutrition choices, including a high intake of sugar. There is currently a gap in our knowledge about the dietary intake of sugar in young New Zealand children. Objectives: To describe total sugar intake and describe differences in total sugar intake based on anthropometry, demographic characteristics and feeding practices in New Zealand 1-3.9-year-olds. Methods: Data from the Young Foods New Zealand study (YFNZ) were used. The current study was a cross-sectional study of young New Zealand children (n=289) aged 1-3.9 years living in Auckland, Wellington, and Dunedin. Two non-consecutive 24-hour diet recalls were administered to parents/caregivers using the triple pass method, and analysed for intake of total sugar, energy, carbohydrate, protein, fat, and fibre. Length, height was measured using a portable stadiometer for children and weight using adult weight scales. BMI z-score was calculated using World Health Organization reference data. Demographic (age, sex, ethnicity, deprivation, parental education), feeding method and food pouch use were measured using a questionnaire. Independent sample t-tests determined the differences in total sugar intake between age and sex. Analysis of Covariance Tests (ANCOVA) tests determined the differences in total sugar intake between BMI z-score classification, feeding method, and demographics. Results: Mean (SD) total sugar intake was 67.3 (15.1) g/day which contributed 22.9 (4.4) % of total energy. Toddlers (n=108) consumed a mean total sugar intake of 65.2 (16.9) g/day which contributed 23.7 (5.1) % of total energy and pre-schoolers (n=181) consumed 68.5 (13.9) g/day which contributed 22.4 (3.8) % of total energy. Boys (n=142) consumed a mean total sugar intake of 67.8 (15.3) g/day which contributed 22.7 (4.4) % of total energy and girls (n=147) consumed 66.8 (15.0) g/day which contributed 23.1 (4.4) % of total energy. Total sugar intake (g/day) varied by BMI z-score category (p=0.004), but not % of total energy (p=0.14). Children who were obese (n=31) had a higher intake of total sugar (g/day) than normal or underweight children (n=148), 75.4 (17.3) vs 65.6 (14.9) respectively, (p=0.006), and overweight children (n=70), 69.4 (14.8), but not significantly (p=0.19). 4 European children (n=125) consumed 66.3 (12.7) g which contributed 22.7 (3.7) % of total energy per day. Māori children (n=75) consumed 69.7 (17.7) g/day which contributed 24.1 (5.2) % of total energy. Pasifika children (n=47) consumed 67.8 (16.0) g/day which contributed 22.4 (4.7) % of total energy. Asian/other children (n=42) consumed 65.3 (15.8) g/day which contributed 21.9 (4.0) % of total energy. Total sugar intake in g/day and % of total energy did not vary by ethnicity (p=0.25) and (p=0.07), deprivation score (p=0.57) and (p=0.25), parental education (p=0.94) and (p=0.55) or feeding method (p=0.63) and (p=0.9), respectively. Total sugar intake (g/day) varies by the number of pouches consumed (p=0.01). Children who consumed 7-14 pouches per week (n=25) had a higher total sugar intake (g/day) compared to children who consumed 1-6 pouches (n=112), 74.7 (19.6) vs 65.3 (14.3) g/day, respectively (p=0.011), but not significantly higher than children who consumed none (n=150) 67.3 (14.2) g/day, (p=0.052). % of total energy from total sugar intake varied by the number of pouches consumed (p<0.001). Children who consumed 7-14 pouches had a higher total sugar intake (% E) than children who consumed none 26.1 (5.2) vs 22.1 (4.1), respectively (p<0.001), and children who consumed 1-6 pouches 23.1 (4.1), (p=0.004). Conclusion: In this cohort of young New Zealand children, total sugar intake contributed 22.9% to daily energy intake. Total sugar intake was higher in children classified as obese compared with children who were normal or underweight. Total sugar intake in g/day and % of total energy from total sugar was higher in children who consumed seven or more pouches per week compared with children who consumed less than seven. There were no differences in total sugar intake according to ethnicity, deprivation, parental education or feeding method.
Keywords: total sugar; dietary intake; young children; 321005 Public health nutrition